[18]Annulene put into a new perspective. - Lungerich, Dominik; Nizovtsev, Alexey; Heinemann, Frank Wilhelm; Hampel, Frank; Meyer, Karsten; Majetich, George; Schleyer, Paul V. R.; Jux, Norbert (Chemical Communications, 2016)
New insights into [18]annulene were gained by looking more closely at its X-ray structure, revealing a close face-to-face stacking of 3.16 Å in a herringbone-like crystal packing. Hexadehydro[18]annulene was co-crystalized in a benzene matrix, demonstrating the stabilizing role of intercalated solvent molecules in solid annulenes.

Synthesis of differently substituted tacn-based ligands: Towards the control of solubility and electronic and steric properties of uranium coordination complexes - Nizovtsev, Alexey; Scheurer, Andreas; Kosog, Boris; Heinemann, Frank Wilhelm; Meyer, Karsten (European Journal of Inorganic Chemistry, 2013)
Starting from phenols ArOH (5) and the anisole derivative 3,5-di-tert-butyl-2-methoxybenzyl bromide (13), a series of new tacn-based ligands (ArOR)tacn (2) have been synthesized with substituents of varying bulkiness and electronic nature at the ortho and para positions with respect to the oxygen coordination site. It was observed that these groups not only determine the steric shielding and solubility properties of 2, but also deactivate the reactivity of the phenols in the modified Mannich reaction when electron-withdrawing groups are introduced at the para position in 5. Treatment of the ligands with UCl in thf led to the isolation of four uranium(IV) chloro complexes [( ArO)tacnUCl] (14), which were characterized by different spectroscopic and physical methods (e.g., H NMR, UV/Vis, SQUID), corroborating the +4 oxidation state in 14. Single-crystal X-ray structure analyses revealed that 14a·CH Cl·CHCN and 14b·1.25CH Cl crystallize in the chiral, orthorhombic space group P222 [a = 24.934(3), b = 27.941(3), c = 9.045(1) Å, V = 6302(2) Å, Z = 4] and the chiral, hexagonal space group P6 [a = 22.097(3), c = 17.941(2) Å, V = 7587(2) Å, Z = 4], respectively. Interestingly, complexes 14a,b self-organize in the solid state into homochiral 1D polymeric superstructures as a result of weak intermolecular C-H⋯Cl contacts. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Uranium-mediated reductive conversion of CO2 to CO and carbonate in a single-vessel, closed synthetic cycle - Schmidt, Anna-Corina; Nizovtsev, Alexey; Scheurer, Andreas; Heinemann, Frank Wilhelm; Meyer, Karsten (Chemical Communications, 2012)
The new neopentyl (Neop)-substituted tris(aryloxide) U(iii) complex [((ArO)tacn)U] reacts with CO to form CO and the bridging carbonate complex [(( ArO)tacn)U(μ-CO )]. The uranium(iv) bridging oxo [((ArO) tacn)U(μ-O)] has been determined to be the intermediate in this reaction. For the first time, both U(iv) complexes can be reduced back to the U(iii) starting material. Thus, with KC as reductant, [((ArO)tacn)U] engages in a synthetic cycle, in which CO is converted to CO and CO . © 2012 The Royal Society of Chemistry.